THE INFLUENCE OF SMARTPHONE APPLICATION ON THE HYGIENE BEHAVIOR OF EXTERNAL REPRODUCTIVE ORGAN OF FEMALE STUDENTS IN 1st SEYEGAN SLEMAN JUNIOR HIGH SCHOOL - Suherni Suherni; Ilma Aptaningrum (Proceedings of the International Conference on Applied Science and Health, 2019)
Introduction: Adolescents is a period of the human development cycle, which is a transition between childhood and adulthood. In this transition many things must be considered one of them is the hygiene of reproductive organ. Hygiene of the reproductive organs, especially the external parts, is very closely related to prevent the reproductive organs from disease. Today is a digital era, most peoples activities used a smartphone including in finding and obtaining information. The use of smartphones at this timecan affect the behavior of everyone, especially teenagers. One of them is the hygiene behavior of the reproductive organs. This research is to know the influence of smartphone application on the hygiene behavior of external reproductive organ female students of Seyegan Sleman Junior High School. Methods: This research used an experimental method with questionnaire-based survey (pre-test and post-test) was conducted in 90 teenage girls. Results: The influence of source information variables, parent’s work and parent's income on behavior were significant (p <0.05). Clinically / practically for respondents exposed to electronic information sources, their behavior is higher at 3.57 compared to non-electronic ones. As for the status of parents who work privately, their behavior is higher by 2.69 compared to those of Civil Servant For the income of parents > = average minimum wage, the level of behavior is higher by 5.34 compared to the income of their parents < average minimum wage. The influence of the information source variable, the work of parents and parent'S income towards behavior is 15 percent. Conclusions: There is a significant difference between the pre and post effects of smartphone applications on the behavior and knowledge of teenage girl reproductive organs hygiene Seyegan Sleman 1 Junior High School Keywords : Adolescents, Hygiene of reproductive organ, Reproductive organ